STRATEGI PENANAMAN JIWA KEWIRAUSAHAAN PADA SISWA DI UPT SPF SD INPRES GONTANG KOTA MAKASSAR - Ariani S (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to find out: (1) Strategies for Instilling an Entrepreneurial Spirit in Students at UPT SPF SD Inpres Gontang; and (2) Obstacles in instilling an Entrepreneurial Spirit in Students at UPT SPF SD Inpres Gontang. This research is a qualitative research with a descriptive approach. The subjects in this study were the principal and teacher of SD Inpres Gontang. Data collection techniques use interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing/verification The results of the research (1) strategies for instilling an entrepreneurial spirit in students at Inpres Gontang Elementary School are carried out by integrating the curriculum with entrepreneurial values in the implementation of learning, making learning implementation plans and linking themes that contain the cultivation of an entrepreneurial spirit, displaying images, videos and telling stories of successful entrepreneurial entrepreneurs, making handicrafts and carrying out market day activities as an effort to instill an entrepreneurial spirit to  Learners. (2) obstacles to the cultivation of an entrepreneurial spirit in students at Inpres Gontang Elementary School such as the lack of interest of students, the theme of entrepreneurship that is not yet in the package book, the lack of family support and lack of human resources (teachers) who have basic entrepreneurship, as well as the lack of creativity and innovation of learning methods from teachers. Keywords : Strategies, Entrepreneurial Spirit, Elementary School